Exploring Jordanian nurses’ attitudes toward conducting nursing research: cross-sectional study from Jordan - Al-Duhoun, Ahmad Hussein; Alhusban, Raya Y.; Tarawneh, Fatimah S.; Al-Olaimat, Kamlah A.; Atout, Maha (Frontiers in Medicine, 2025)
BackgroundResearch is essential in nursing to augment the existing knowledge foundation underpinning the field, from education through practice and administration. To date, few studies have explored this topic in Jordan or the broader Middle Eastern region, and this study addresses this important gap.ObjectiveThe objective of the current study was thus to examine the perspectives of Jordanian nurses concerning the practice of nursing research.MethodsIn a cross-sectional descriptive study, 220 nurses from public, private, and academic institutions in Jordan were approached using a convenience sampling to complete the Boothe Attitudes Toward Nursing Research Scale.ResultsThe results showed that the overall mean score of all Boothe subscales was 3.289, SD = 0.968, reflecting practitioners’ uncertainty as a cohort in their attitudes toward research. Nurses exhibited somewhat favorable attitudes regarding the incentives and benefits associated with conducting nursing research, however (mean = 3.439, SD = 1.038). Statistically significant effects were also seen for participants’ level of education (F (2,218) = 39.993, p < 0.000), their personal interest in research (F (2,218) = 26.251, p < 0.000), and whether they received an incentive for doing studies.ConclusionThis study suggests that if hospital administrators work to collaborate with the academic institution to advance and facilitate higher education, they can improve patient outcomes by ensuring that more nursing practices are safe and evidence-based.